Evaluating children with vestibular migraine through vestibular test battery: A cross-sectional investigation - Zhang, Fan; Shen, Jiali; Zhu, Qi; Wang, Lu; Ma, Xiaobao; He, Baihui; Yang, Yang; Wang, Wei; Chen, Xiangping; Zhang, Qing; Jin, Yulian; Duan, Maoli; et al. (Frontiers in Neurology, 2022)
Objective: The present study aimed to investigate the status of vestibular function in children with vestibular migraine of childhood (VMC) reflected by vestibular function test battery and explore the pathophysiological implication of these instrument-based findings. Methods: The clinical data of 22 children (mean age 10.7±2.9 years) with VMC who met the diagnostic criteria of the Barany Society were collected from September 2021 to March 2022. A vestibular function test battery on these children included a caloric test, video head impulse test (vHIT), cervical vestibular-evoked myogenic potential (cVEMP), and ocular vestibular evoked myogenic potential (oVEMP); these parameters were triggered by air-conducted sound (ACS) and galvanic vestibular stimulation (GVS). The subjects were further divided into two groups: <3 months and >3 months according to the disease duration from symptom onset. The functional abnormalities and their characteristics reflected by the vestibular test battery, as well as the outcomes in children with or without aura were analyzed. Results: (1) The abnormal rate of caloric test was 15.8% and that of vHIT was 0%. The response rates of ACS-cVEMP and ACS-oVEMP were 100% and 90.5%, respectively. The response rates of GVS-cVEMP and GVS-oVEMP were 100% and 88.9%, respectively. (2) No statistical difference was observed in the abnormal rate of the caloric test (P=0.55) and the response rate of ACS-oVEMP (P=0.21) between the two groups, irrespective of the course duration. (3) No statistical difference was detected in the abnormal rate of caloric test (P=0.53) and the response rate of ACS-oVEMP (P=1.00) in children with or without aura. Conclusion: Vestibular function status comprehensively reported by the vestibular test battery did not show an aggravation with the disease duration in children with VMC. Also, it was not affected by the existence of aura in children with VMC. The high abnormal rates of caloric test and oVEMPs (ACS-oVEMP and GVS-oVEMP) suggested that the lateral semicircular canal (low-frequency function component), the utricle, and the superior vestibular conduction pathway might be involved in VMC.